A Multi-Sensory In-Store Virtual Reality Customer Journey for Retailing: A Field Study in a Furniture Flagship Store - Michele Fiorentino; Marina Ricci; Alessandro Evangelista; Vito Modesto Manghisi; Antonio Emmanuele Uva (Future Internet, 2022)
The choice of furniture in a retail store is usually based on a product catalog and simplistic product renderings with different configurations. We present a preliminary field study that tests a Multi-Sensory In-Store Virtual Reality Customer Journey (MSISVRCJ) through a virtual catalog and a product configurator to support furnishings sales. The system allows customers to stay immersed in the virtual environment (VE) while the sales expert changes the colors, textures, and finishes of the furniture, also exploring different VEs. In addition, customers can experience realistic tactile feedback with in-store samples of furniture they can test. The journey is implemented for a furniture manufacturer and tested in a flagship store. Fifty real customers show positive feedback in terms of general satisfaction, perceived realism, and acceptance. This method can increase purchase confidence, reduce entrepreneurial costs, and leverage in-store versus online shopping.